Neural Mechanisms of Observational Learning: A Neural Working Model - Kang, Weixi; Pineda Hernández, Sònia; Mei, Jie (Frontiers in Human Neuroscience, 2021)
Humans and some animal species are able to learn the stimulus-response (S-R) associations by observing others' behavior, and it saves energy and time and avoids the danger of trying the wrong actions. Observational learning (OL) depends on the capability of mapping the actions of others into our own behaviors, then process outcomes, and combine these knowledges to serve our goals. Observational learning plays a central role in the learning social skills, cultural knowledge, and tool use. Thus, it is one of the fundamental processes in which infants learn about and from adults (Byrne and Russon, 1998; Meltzoff et al., 2009). In this paper, we review current methodological approaches employed in observational learning research, highlight the important role of the prefrontal cortex and cognitive flexibility to support this learning process, develop a new neural working model of observational learning, illustrate how imitation relates to observational learning, and provide directions for future research.